BUSINESS INDEPENDENCE IN SOCIAL CAPITAL REVIEW FOR ASAR FISH BUSINESS COMMUNITIES IN LAHA VILLAGE, TELUK AMBON DISTRICT, AMBON CITY - Derek Bakarbessy (Fakultas Ilmu Sosial dan Ilmu Politik, 2021)
This study aims to analyze business independence in terms of social capital for asar fish business community in Laha Village, Teluk Ambon District, Ambon City. This research is an explanatory research for two months, from June to August 2021. The population in this study are asar fish business actors in Laha Village, Teluk Ambon District, Ambon City. A sample of 78 people was determined by a simple random technique. The data analysis used is path analysis supported by qualitative descriptive interpretation. The data were analyzed with the help of Lisrel software version 8.50. The results showed that the influence of trust, norms and network variables on self-reliance through business development variables was 96%, which indicates that asar fish business development can be improved through strengthening social capital in the form of trust, norms and networks which will ultimately increase the independence and economic capacity of the farmers. businessmen.